A needs-based workforce model to deliver tertiary-level community mental health care for distressed infants, children, and adolescents in South Australia: a mixed-methods study. (June 2018) - Segal, Leonie; Guy, Sophie; Leach, Matthew; Groves, Aaron; Turnbull, Catherine; Furber, Gareth
Summary: Background: High-quality mental health services for infants, children, adolescents, and their families can improve outcomes for children exposed to early trauma. We sought to estimate the workforce needed to deliver tertiary-level community mental health care to all infants, children, adolescents, and their families in need using a generalisable model, applied to South Australia (SA). Methods: Workforce estimates were determined using a workforce planning model. Clinical need was established using data from the Longitudinal Study of Australian Children and the Young Minds Matter survey. Care requirements were derived by workshopping clinical pathways with multiprofessional panels, testing derived estimates through an online survey of clinicians. Findings: Prevalence of tertiary-level need, defined by severity and exposure to childhood adversities, was estimated at 5–8% across infancy and childhood, and 16% in mid-adolescence. The derived care pathway entailed reception, triage, and follow-up (mean 3 h per patient), core clinical management (mean 27 h per patient per year), psychiatric oversight (mean 4 h per patient per year), specialised clinical role (mean 12 h per patient per year), and socioeconomic support (mean 12 h per patient per year). The modelled clinical full-time equivalent was 947 people and budget was AU$126 million, more than five times the current service level. Interpretation: Our novel needs-based workforce model produced actionable estimates of the community workforce needed to address tertiary-level mental health needs in infants, children, adolescents, and their families in SA. A considerable expansion in the skilled workforce is needed to support young people facing current distress and associated family-based adversities. Because mental illness is implicated in so many burgeoning social ills, addressing this shortfall could have wide-ranging benefits. Funding: National Health and Medical Research Council (Australia), Department of Health SA.